Global Outlook for Ice and Snow: Highlights - United Nations Environment Programme (United Nations Environment Programme, 2016)
Ice and snow are important components of the Earth’s climate system and are particularly sensitive to global warming. Over the last few decades the amount of ice and snow, especially in the Northern Hemisphere, has decreased substantially, mainly due to human-made global warming. Changes in the volumes and extents of ice and snow have both global and local impacts on climate, ecosystems and human well-being. Snow and the various forms of ice play different roles within the climate system. The two continental ice sheets of Antarctica and Greenland actively influence the global climate over time scales of millennia to millions of years, but may also have more rapid effects on, for example, sea level. Snow and sea ice, with their large areas but relatively small volumes, are connected to key interactions and feedbacks at global scales, including solar reflectivity and ocean circulation. Perennially frozen ground (permafrost) influences soil water content and vegetation over continental scale northern regions and is one of the cryosphere components most sensitive to atmospheric warming trends. As permafrost warms, organic material stored in permafrost may release greenhouse gases into the atmosphere and increase the rate of global warming. Glaciers and ice caps, as well as river and lake ice, with their smaller areas and volumes, react relatively quickly to climate effects, influencing ecosystems and human activities on a local scale. They are good indicators of climate change